Duplication cyst of the pylorus: a rare cause of gastric outlet obstruction - Arshad, Muhammad (BMJ Case Rep, 2018)
Alimentary tract duplications are a rare congenital malformation. They can present with varied symptoms owing to the locality of the duplication, along the gastrointestinal tract. Out of these duplications, the ones along the pylorus are the most rare. These are usually only diagnosed intraoperatively, as it is not a common differential on imaging due to its rarity. In lieu of the literature currently available, pyloric duplication cyst can present anytime from 1 week of age to 5 years, with some cases being detected antenatally due to the prevalence of regular antenatal scanning. Surgery remains the main stay of treatment with the goal of complete excision of the cyst and complete removal of the cyst mucosal lining. We report the case of a 5-year-old girl, which to our knowledge is the first ever reported case from Karachi, Pakistan.